Sources of support related to exclusive breastfeeding behavior - Etrawati, Fenny; Putri, Cindi Amelia; Budi, Iwan Stia; Angraini, Rima (Riset Informasi Kesehatan, 2024)
Background: The South Sumatra Health Office (2022) reported that the exclusive breastfeeding rate in OKI Regency was 71.0%, which is still below the national target of 80%. The purpose of this study was to identify the sources of support and their relationship with maternal behavior in exclusive breastfeeding. Method: This study used a qualitative research design involving 12 mothers with infants aged 6-12 months as key informants, as well as 11 expert informants, including the head of the puskesmas, the nutrition program coordinator, 3 midwives, and 6 posyandu cadres. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. Source and data triangulation were used for validation. Results: Parents supported early complementary feeding by recommending items like Zamzam water, coffee, bananas, porridge, rice with sugar, and honey. Although health workers emphasized exclusive breastfeeding, the absence of visual aids like videos limited the impact. To improve exclusive breastfeeding, stronger educational efforts and diverse media use in outreach are essential. Conclusion: The results indicated that parents provided support for early complementary feeding, recommending items such as Zamzam water, coffee, pisang kepok (a type of banana), porridge, rice with sugar, and honey. Health workers had communicated the importance of exclusive breastfeeding persuasively, but the lack of visual aids, such as educational videos, during socialization and counseling sessions may have reduced the effectiveness of information delivery. To enhance exclusive breastfeeding practices, more intensive educational efforts and the use of varied media in health worker outreach to breastfeeding mothers are needed.